Odpowiedzi

2009-12-30T17:26:33+01:00
|6 r13 - 17|-|17 - 6 r13| = -45.24
|2 - |2 - r5 ||= -r5
|r3 - | - r3 - 1 ||= -1+2r3
Najlepsza Odpowiedź!
2009-12-30T17:31:46+01:00
A) |6√13 - 17| - |17 - 6√13|= 6√13 - 17 - (-17 + 6√13)= 6√13 - 17 + 17 -6√13= 0
b) |2 - |2 - √5 ||=|2 - (-2 +√5)|= |2 +2 - √5| = 4 - √5
c) |√3 - | - √3 - 1 || = |√3 -(√3 + 1)|= |√3 - √3 - 1| = |-1| = 1
d) podałeś takie same jak c)
2009-12-30T17:40:32+01:00
A) |6√13-17|-|17-6√13|=6√13-17-(6√13-17)=6√13-17-6√13+17=0
b)|2-|2-√5||=|2-(√5-2)|=2+2-√5
c)|√3-|-√3-1||=|√3-(√3+1)|=|-1|=1